Activación conductual y depresión en adultos. - Freire Villacís, Alejandra Estefanía (2025)
This study analyzed the application of Behavioral Activation (BA) therapy and its effects on depression in adults. A descriptive approach was used, drawing on high-impact, indexed databases such as SCOPUS, Web of Science, and PubMed. The selection of articles included in this systematic review considered studies conducted since 2014 based on inclusion and exclusion criteria as outlined by the PRISMA methodology. The study comprised 21 articles subjected to a quality assessment using the Critical Review Form–Quantitative Studies (CRF-QS) instrument. The results identified the techniques described by Barraca and Pérez-Álvarez (2015): identification of values, activity scheduling, monitoring of activities and mood, assessment of difficulties, rating of experienced pleasure and achievement when performing activities, exploration of alternative behaviors, relapse prevention, and physical exercise. The studies also showed that BA is effective in reducing depressive symptoms, making it a viable and accessible alternative.